Low-temperature thermal properties in the CePd3Bx system - Sereni, J.; Nieva, G.; Kappler, J. P.; Besnus, M.J.; Meyer, A.; Sereni, Julián; Nieva, Gladys (IOP Publishing, 1986)
Fil: Sereni, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina